Systematic Literature Review: Digitalisasi dalam Layanan Bimbingan dan Konseling - Purnomo, Agus (Journal of Innovation in Teaching and Instructional Media, 2025)
The purpose of this study is to determine the progress of the era related to the increase in technology in the modern era. Logical thinking plays an important role in the development of all fields of science, especially the philosophy of science. The role of philosophy of science in guidance and counseling in the digital era is greatly influenced by technological advances in the digital era. To capture, master, and treat innovation well and appropriately, continuation must be the main source of funding. The purpose of this study is to determine how much science has developed in the digital era by studying the philosophy of science about guidance and counseling in the digital era. This study uses a systematic literature review method or SRL. The data collected are based on the results of previous similar studies. The 12 national journals obtained and used in this study came from the Google Scholar database. This study found that there is a relationship between the role of digitalization in providing guidance and counseling in each educational unit.